Analysis of Switching Conditions of IGBTs in Modified Sine Wave qZSIs Operated with Different Shoot-Through Control Methods - Vinnikov, D.; Roasto, I.; Zakis, J.; Ott, S.; Jalakas, T. (Elektronika ir Elektrotechnika, 2011)
This paper discusses two novel shoot-through control methods specially developed for the modified sine wave qZSI -the pulse width and phase shift modulation. The operating conditions of IGBTs are experimentally examined in both control methods and the resulting advantages of each method are explained. Ill. 16, bibl. 6, tabl. 6 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.354